Mitochondria, Cognitive Impairment, and Alzheimer's Disease. (25th June 2009) - Mancuso, M.; Calsolaro, V.; Orsucci, D.; Carlesi, C.; Choub, A.; Piazza, S.; Siciliano, G.
Abstract : To date, the beta amyloid (Aβ ) cascade hypothesis remains the main pathogenetic model of Alzheimer's disease (AD), but its role in the majority of sporadic AD cases is unclear. The "mitochondrial cascade hypothesis" could explain many of the biochemical, genetic, and pathological features of sporadic AD. Somatic mutations in mitochondrial DNA (mtDNA) could cause energy failure, increased oxidative stress, and accumulation of Aβ, which in a vicious cycle reinforce the mtDNA damage and the oxidative stress. Despite the evidence of mitochondrial dysfunction in AD, no causative mutations in the mtDNA have been detected so far. Indeed, results of studies on the role of mtDNA haplogroups in AD are controversial. In this review we discuss the role of the mitochondria, and especially of the mtDNA, in the cascade of events leading to neurodegeneration, dementia, and AD.